2019
DOI: 10.2174/0929867325666180316115726
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional HDL as a Therapeutic Target for Atherosclerosis Prevention

Abstract: Hypercholesterolemia is one of the main risk factors for the development of atherosclerosis. Among the various lipoprotein classes, however, high density lipoproteins (HDL) are inversely associated with the incidence of atherosclerosis, since they are able to exert a series of atheroprotective functions. The central role of HDL within the reverse cholesterol transport, their antioxidant and anti-inflammatory properties and their ability to preserve endothelial homeostasis are likely responsible for HDL-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 214 publications
1
26
0
Order By: Relevance
“…HDL particles are recognized as a protective factor against cardiovascular disease since they promote several atheroprotective functions [ 3 ] and their increment by 1 mg/dL is linked to an average decrease of 3% in the risk for development of CVD [ 4 , 5 ]. During inflammation in acute phase or in chronic situations (e.g., different dysmetabolic diseases), HDLs undergo significant remodeling in their lipid as well as in their proteome content [ 6 10 ], resulting in impaired functions that lead to CVD [ 11 ]. Proatherogenic HDL dysfunctionality may include reduced antioxidation function [ 12 14 ]‚ impaired cholesterol efflux [ 7 , 15 ], and reduced nitric oxide production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…HDL particles are recognized as a protective factor against cardiovascular disease since they promote several atheroprotective functions [ 3 ] and their increment by 1 mg/dL is linked to an average decrease of 3% in the risk for development of CVD [ 4 , 5 ]. During inflammation in acute phase or in chronic situations (e.g., different dysmetabolic diseases), HDLs undergo significant remodeling in their lipid as well as in their proteome content [ 6 10 ], resulting in impaired functions that lead to CVD [ 11 ]. Proatherogenic HDL dysfunctionality may include reduced antioxidation function [ 12 14 ]‚ impaired cholesterol efflux [ 7 , 15 ], and reduced nitric oxide production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding ionizing radiation even in low doses will aggravate the risk of cardiovascular disease, primarily causing endothelial cell damage which leads to the process of atherosclerosis [20,21]. HDL reduces the deposition of cholesterol into tissues thereby playing an anti-atherosclerotic role by preventing the occurrence and development of atherosclerosis [22]. Our clinical studies demonstrated that radiation exposure remained a high-risk factor for the occurrence of atherosclerosis however HDL could effectively reduce such risk.…”
Section: Discussionmentioning
confidence: 66%
“…Although some studies suggested that moderate ultraviolet radiation can prevent cardiovascular disease [19]. Low dose of ionizing radiation will increase the risk of cardiovascular disease, mainly cause endothelial cell damage and participate in the process of atherosclerosis [20,21].HDL plays an anti atherosclerotic role by reducing the deposition of cholesterol in tissues, thus limiting the occurrence and development of atherosclerosis [22].Our clinic studies showed that radiation exposure was high risk factor during atherosclerosis prevalence, HDL superior to reduce this risk. Radiation can induce apoptosis through oxidative stress, during the cell experiment, MAECs apoptosis increased and HDL may protect [23].…”
Section: Discussionmentioning
confidence: 74%